Colton 911 : cowboy's rescue - Ferrarella, Marie (Harlequin romantic suspense, 2019)
When Magnolia “Maggie” Reeves receives a puzzling map from her former father-in-law, she can<U+2019>t resist searching for clues<U+2014>even in a hurricane! Fortunately, search-and-rescue cowboy Jonah Colton is there to save the day. But when the duo find a mummified body, they<U+2019>re plunged straight into an abyss of danger. And even as they stumble headlong into a dazzling attraction, they<U+2019>re also fighting for their lives<U+2026>